Water relations of apple and influence on fruit quality (minireview) - Nemeskéri, E. (International Journal of Horticultural Science, 2007)
The saving of soil water content and the improvement of adaptability of plants to periodical insufficient water and use of deficit irrigation technology become more important because of the occurrence of frequently dry periods. The water use efficiency of apples can be increased by the choice of appropriate rootstocks and determination of water requirement of varieties that depend on their growing periods and climatic factors. Depletion of soil water resources need to develop efficient irrigation techniques for quality apple production. A new deficit irrigation strategy (PRD) has been developed that based on partial water supply of root-zone. This does not result a decrease in the sizes and yield of the fruit. The larger fruit size and lower firmness in frequently irrigated trees can result in excessive internal growth stresses that cause higher rate of fruit splitting. Many studies revealed the relationship between irrigation and yield quantity. Recent researches investigate the effects of irrigation on apple fruit quality particularly on the colouration and post-harvest quality. Use of cooling irrigation improves the development of coluour an apple fruit but its schedule can influence on the incomes. Aroma volatiles are responsible for odour and contribute to overall flavour of the fruit and its processed products. Deficit irrigation had only affects some volatile aroma but no the all of concentrations in apple fruit. In the future the high apple quality for consumers could be provided with improvement of transpiration-yield model based on the water requirement of varieties and economic irrigation schedules.